2018
DOI: 10.1016/j.ygyno.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

The Onclarity Human Papillomavirus Trial: Design, methods, and baseline results

Abstract: This report provides demographic information, cytology findings, HPV genotype information, and histopathology for participants in the baseline phase of this trial and offers further evidence to support genotype-specific screening for cervical cancer and precancer. Clinical Trial Registry URL:https://clinicaltrials.gov/ct2/show/NCT01944722.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 27 publications
3
71
0
Order By: Relevance
“…[8][9][10] In contrast, the prevalence of precancer, defined as cervical intraepithelial neoplasia grade 3 (CIN3) and adenocarcinoma in situ (AIS), is on the order of 0.5-1%. 11,12 As it is neither possible nor clinically desirable to refer all HPV-positive women to colposcopy, a triage strategy for HPV-positive women is needed to identify the women who would benefit most from immediate referral to colposcopy. For example, in the Netherlands, a target referral rate of 2% of screened women is considered "ideal," producing a ratio of 2-4 colposcopies per CIN3 detected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] In contrast, the prevalence of precancer, defined as cervical intraepithelial neoplasia grade 3 (CIN3) and adenocarcinoma in situ (AIS), is on the order of 0.5-1%. 11,12 As it is neither possible nor clinically desirable to refer all HPV-positive women to colposcopy, a triage strategy for HPV-positive women is needed to identify the women who would benefit most from immediate referral to colposcopy. For example, in the Netherlands, a target referral rate of 2% of screened women is considered "ideal," producing a ratio of 2-4 colposcopies per CIN3 detected.…”
Section: Introductionmentioning
confidence: 99%
“…Recent epidemiologic data have shown that the risk of CIN3 for some of those 12-other hrHPV genotypes, such as HPV31 or 33, is on par with HPV18. 11,17 Therefore, following the concept of equal management for equal risk, questions have arisen as to how extended genotyping might shift the balance among the two screening groups created by triage of screen positives: those referred for immediate colposcopy and those who can safely be deferred for follow-up testing after 12 months.…”
Section: Introductionmentioning
confidence: 99%
“…The BD Onclarity™ HPV Assay provides results on an automated platform (BD Viper LT™ System) and offers genotyping with individual reporting of types 16, 18, 31, 45, 51 and 52 and identification of three groups of types: 33/58, 56/59/66 and 35/39/68. The Onclarity HPV test is internationally validated on both SurePath and Thinprep LBC media for use in primary HPV screening and has recently received FDA approval for primary screening in women over 25 years in the United States . To investigate the risk of disease arising from the individual HPV genotypes, we used Bayesian data analysis which provides a natural and principled way of modeling risk in subjects with multiple genotype infections.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Many HR-HPV screening tests have since been developed to improve upon the performance of HC2 test. 14,18,19 In this study, we reported the promising result of such an effort. CerviHPV results in terms of the levels and types of HPV infection, thus confirming very low levels of HR-HPV infection in these cases ( The methodology and design of CerviHPV test are very similar to those of another widely used HR-HPV detection assay, cobas HPV Test (cobasHPV), 30 which was the first HR-HPV test approved by FDA for primary cervical cancer screening.…”
Section: Discussionmentioning
confidence: 73%
“…Third, it has been well documented that HC2 probes can cross react with many LR‐HPV types, leading to false positive result . Many HR‐HPV screening tests have since been developed to improve upon the performance of HC2 test . In this study, we reported the promising result of such an effort.…”
Section: Discussionmentioning
confidence: 79%